Os métodos de controle dos serviços públicos nas concessões de transportes municipais - Silva, Jacob Paschoal Gonçalves da (2016)
This study aims to determine the expansion of control that occurred as a result of the public service concept remodeling. This occurred when eventually brought to the field of law related extra-legal terms the other sciences in the pursuit of quality and efficiency in the public sector. This situation has developed in the public service concessions, gaining prominence in municipal concessions of public transport with the advent of Urban Mobility Act. All this, in the light of changes occurring in Administrative Law, linked to the evolution of the concept of public service as a result of State transformations over the years, especially the regulatory function of regulatory agencies. These control methods not only cover the analysis of legality; the aim is to also control results turned the pursuit of quality and administrative efficiency, economy and other concepts that define an appropriate service in the public service concessions, especially correlated to the municipal transport, both by regulatory agencies, as well as by other entities, such as the judiciary, popular control of the Audit Courts and the Administration itself. On the other hand, put up the control limits and the form of accountability of the agents participating in the expedition of normative acts of regulatory agencies. These excessive and illegal acts, which are taken from the order on the grounds of proportionality and of its elements, including scoring decisions of the Judiciary, who performed in this light control over administrative discretion. Therefore, we seek to demonstrate what would be the control limits conducted within the public service concessions in providing quality service. The preparation of this work came from a methodological approach in Brazilian literature, as well as foreign founded in a dogmatic analysis, especially in the public service notion of definitions and on proportionality. The conclusion is shown that efficiency is one of the vectors in effecting the quality of public service and the control performed in the internal and external environment is gradually widening the search for better results to public service users, effecting fundamental rights.